Self-Reported Spiritual Care among Moslem ICU Nurses in the Rural Area of Indonesia - Sulistyanto, Benny Arief; Khonita, Intana Vita Silma; Irnawati, Irnawati; Wati, Nenden Lesmana (Proceedings Series on Health & Medical Sciences, 2022)
Spiritual care is very important particularly for patients who are experiencing critical conditions. Although the priority of critical care is to maintain the function of the organ systems and to improve the patient’s health condition, the patient’s spiritual care should not be ignored. This study aimed to identify spiritual care practice among ICU Nurses at public hospitals in rural areas. This survey study used the NSCTS (Nursing Spiritual Therapeutics Scale) questionnaires to identify spiritual care in the ICU wards. This study involved 39 ICU nurses who work in the three public hospitals of Pekalongan Regency, Central Java Indonesia (Kajen Hospital, Kraton Hospital, and Bendan Hospital). Data were analyzed by using Microsoft excel. The result of this study revealed that the average spiritual care among ICU nurses is 3.79. In the context of the spiritual care item question, the highest mean score was "Offered to pray with a patient," whereas the lowest was "Documented spiritual care you provided in a patient chart." Despite the study limitation, this study encourages the ICU nurses to record the spiritual nursing care into nursing care sheets.